2016
DOI: 10.1007/s00737-016-0604-x
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making about fertility preservation—qualitative data on young cancer patients’ attitudes and needs

Abstract: The aim of the study was to get deeper insight into the significance of fertility in cancer patients, their attitude towards fertility preservation (FP), decisional conflicts, and patient's needs in the decision-making process. Focus groups with 12 female cancer survivors were held and revealed that the significance of fertility was high and attitude towards FP positive. Religious and ethical reservations were not negligible. Standardized decision aids were considered helpful. More support is highly in demand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…Although survival was patients’ primary priority (Crawshaw et al, ; Ehrbar et al, ; Gorman et al, ; Keim‐Malpass et al, ; Komatsu et al, ; Lee et al, ; Peddie et al, ; Penrose et al, ; Snyder & Tate, ; Wilkes et al, ; Yee, Abrol, et al, ), fertility, and correspondingly, the desire and hope of being a parent after cancer were also important to women (Ehrbar et al, ; Hershberger et al, ; Niemasik et al, ; Penrose et al, ). Fertility was perceived as a component of femininity and central to a women's identity (Ehrbar et al, ; Ussher et al, ). Women also expressed apprehension about success rates of FP, effects of FP technologies on the health of future children, vertical transmission of cancer genes and the potential for cancer recurrence (Ehrbar et al, ; Gorman et al, ; Hershberger et al, ; Komatsu et al, ; Niemasik et al, ; Wilkes et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although survival was patients’ primary priority (Crawshaw et al, ; Ehrbar et al, ; Gorman et al, ; Keim‐Malpass et al, ; Komatsu et al, ; Lee et al, ; Peddie et al, ; Penrose et al, ; Snyder & Tate, ; Wilkes et al, ; Yee, Abrol, et al, ), fertility, and correspondingly, the desire and hope of being a parent after cancer were also important to women (Ehrbar et al, ; Hershberger et al, ; Niemasik et al, ; Penrose et al, ). Fertility was perceived as a component of femininity and central to a women's identity (Ehrbar et al, ; Ussher et al, ). Women also expressed apprehension about success rates of FP, effects of FP technologies on the health of future children, vertical transmission of cancer genes and the potential for cancer recurrence (Ehrbar et al, ; Gorman et al, ; Hershberger et al, ; Komatsu et al, ; Niemasik et al, ; Wilkes et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Lack of FP‐related educational resources (King, Quinn, Vadaparampil, Gwede, et al, ; Quinn & Vadaparampil, ; Quinn et al, ; Quinn, Vadaparampil, King, et al, ; Vadaparampil et al, ), time (Ehrbar et al, ; Hershberger et al, ), accessibility to clinics (Hershberger et al, ; King, Quinn, Vadaparampil, Gwede, et al, ; Quinn, Vadaparampil, King, et al, ), costs in regions without FP coverage, (Gorman et al, ; King, Quinn, Vadaparampil, Gwede, et al, ; King, Quinn, Vadaparampil, Miree, et al, ; Niemasik et al, ; Quinn & Vadaparampil, ; Quinn et al, ; Quinn, Vadaparampil, King, et al, ; Snyder & Tate, ; Vadaparampil et al, ), age (King, Quinn, Vadaparampil, Gwede, et al, ; Peddie et al, ), marital/parent status (Corney & Swinglehurst, ; King, Quinn, Vadaparampil, Miree, et al, ; Lee et al, ; Snyder & Tate, ) and culture/religion (Ehrbar et al, ; Quinn & Vadaparampil, ; Quinn, Vadaparampil, King, et al, ; Vadaparampil et al, ) were identified as additional factors posing challenges to FP discussions and decision‐making. Studies reported that oncologists found FP discussions awkward in part because they had no resources to refer to, and because available resources were inappropriate for some patient population (Quinn & Vadaparampil, ; Vadaparampil et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations